Elasto-plastic contact of fractal surfaces - Willner, Kai (Analysis and Simulation of Contact Problems, 2006)
The elasto-plastic normal contact of fractal surfaces is numerically investigated using a halfspace model. Artificial surface data are generated using the structure function, to study the influence of different surface parameters with respect to the load-area relationship and the load-gap relationship. The simulations show that for realistic surface parameters the deformation is always in the plastic range. © Springer 2006.
UnivIS-Import:2015-04-16:Pub.2006.tech.FT.FT-TM.elasto